(untitled) - Floyd, Thomas L (New York, 2018)
For courses in basic electronics and electronic devices and circuitsElectronic Devices, 10th Edition, provides a solid foundation in basic analog electronics and a thorough introduction to analog integrated circuits and programmable devices. The text identifies the circuits and components within a system, helping students see how the circuit relates to the overall system function.Full-colour photos and illustrations and easy-to-follow worked examples support the text's strong emphasis on real-world application and troubleshooting. Updated throughout, the 10th Edition features selected circuits keyed to Multisim V14 and LT Spice files so that students learn how to simulate, analyse, and troubleshoot using the latest circuit simulation software.
Keywords: Thiết bị và dụng cụ điện tử,Electronic apparatus and appliances